Early and Short-Term Interventions in the Gut Microbiota Affects Lupus Severity, Progression, and Treatment in MRL/lpr Mice - Zhang, Yun; Liu, Qiuping; Yu, Yiran; Wang, Mingzhu; Wen, Chengping; He, Zhixing (Frontiers in Microbiology, 2020)
There have been attempts to reveal the possible associations between systemic lupus erythematosus (SLE) and gut microbiota. Using MRL/lpr mice, this study was performed to reveal whether early and short-term interventions in gut microbiota affect lupus. MRL/lpr mice were treated with antibiotics or fecal microbiota transplantation (FMT) before onset. Then, prednisone was used to treat the lupus mice with initially different gut microbiota compositions. The compositions of gut microbiota were assessed by the V3-V4 region of 16S rRNA gene sequence. Early and short-term antibiotics exposure aggravated lupus severity by depleting beneficial gut microbiota for lupus, such as Lactobacillus and Bifidobacterium, and enriching harmful gut microbiota for lupus, such as Klebsiella and Proteus. FMT alleviated lupus severity by renovating the antibiotic-induced dysbiosis of gut microbiota in the following one week after antibiotics exposure. Besides, short-term antibiotics exposure before onset imposed no significant effects on lupus progression, but the following one week of FMT suppressed lupus progression. Moreover, the short-term antibiotics or FMT before onset inhibited the therapeutic efficiency of prednisone on lupus from 9 weeks old to 13 weeks old of MRL/lpr mice. These data demonstrate that the gut microbiota before onset is important for lupus severity, progression and treatment.